2016
DOI: 10.1093/poq/nfw013
|View full text |Cite
|
Sign up to set email alerts
|

The Political Consequences of Latino Prejudice against Blacks

Abstract: A good deal of scholarship examines the effects of prejudice against blacks on public opinion and vote choice in the United States. Despite producing valuable insights, this research largely ignores the attitudes of Latinos-a critical omission, since Latinos constitute a rapidly growing share of the population. Using two nationally representative survey data sets, we find that the level of racial prejudice is comparable for Latinos and non-Hispanic whites. Equally comparable are associations between prejudice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“… 14. These results are consistent with numerous research findings indicating a large impact of prejudice in other domains, such as vote choice and turnout in elections with Black candidates (e.g., Krupnikov and Piston, 2015a; Krupnikov and Piston, 2015b; Krupnikov and Piston, 2016; Krupnikov et al, 2016). This is especially disturbing given that the conditions for prejudice reduction are extremely limited (Lupia et al, 2015).…”
Section: Notessupporting
confidence: 92%
“… 14. These results are consistent with numerous research findings indicating a large impact of prejudice in other domains, such as vote choice and turnout in elections with Black candidates (e.g., Krupnikov and Piston, 2015a; Krupnikov and Piston, 2015b; Krupnikov and Piston, 2016; Krupnikov et al, 2016). This is especially disturbing given that the conditions for prejudice reduction are extremely limited (Lupia et al, 2015).…”
Section: Notessupporting
confidence: 92%
“…Along similar lines, Lopez and Pantoja () reported that evaluations of opportunity‐enhancing affirmative action policies displayed a clear racial rank ordering, with Black Americans displaying the highest levels of support, Whites the least, and Latinos and Asians occupying an intermediate position between these two extremes. Krupnikov and Piston () too found that Latinos’ support for race‐targeted policies in the United States was generally significantly higher than of Whites but significantly lower than that of Blacks.…”
Section: The P‐i Gap: Empirical Foundationsmentioning
confidence: 99%
“…Second and related, the accumulation of evidence suggests that the P‐I gap is causally overdetermined, reflecting the influence of multiple sufficient causes that may vary in significance across different social contexts. Third, as noted in the previous section, explanations of the P‐I gap have primarily evolved to explain the attitudes of White Americans and the extent to which existing theories can account for the more complex, multiracial patterns being identified by recent research remains uncertain (e.g., see Krupnikov & Piston, ; Lopez & Pantoja ; Wodtke, ). These complexities notwithstanding, there is now a critical mass of evidence confirming the central role of: (1) group interests and intergroup competition, (2) beliefs about the nature and underlying causes of inequality, and (3) racial prejudice in explaining (White) opposition to race‐targeted interventions.…”
Section: The P‐i Gap: Empirical Foundationsmentioning
confidence: 99%
See 2 more Smart Citations